Determinants of electronic commerce adoption: Case study among Small and Medium Enterprise (SME) in Klang Valley / Nur Atiqah Zainuddin … [et al.] - Zainuddin, Nur Atiqah; Ismail, Maymunah; Ahmad, Nurul Zamratul Asyikin; Sharif, Sharina; Mazalan, Maz Izuan; Ab Kadir, Mohd Sufian (2017)
Nowdays, electronic commerce or e-commerce is the most important tool in business market especially in digital online marketing. It‘s create more competitive marketing among the business around the world and focusing on Small Medium Enterprise formerly SME. In Malaysia, e-commerce is among the tool use by SME with the role to expand their business that can be reachable by customers. The purpose of this study is to determine the factors affecting adoption of e-commerce by SME in Klang Valley and to identify the most influential factor on e-commerce adoption. A conceptual framework comprises of five factors that are relative advantage, compatibility, complexity, top management support and knowledge and resources constraint is being taken as variables for research. Multiple regression analysis generated is being carried out to test hypothesis and to establish the causal effect of relative advantage, compatibility, complexity, top management support and knowledge and resources constraint towards adoption of e-commerce. The result shows that relative advantage, compatibility, and top management support and knowledge have significant and positive impact on adoption of e-commerce. Therefore this study concluded that relative advantage, compatibility, and top management support and knowledge would increase adoption of e-commerce among SME. Therefore, the government should take initiatives and pay more attention to promote e-commerce among SME because SME has potential market growth and high contribution for economic development in Malaysia.